2017
DOI: 10.1097/dbp.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of Parental Observations on Quality of Life in Australian Children with Down Syndrome

Abstract: Objective There are many challenges to health, functioning and participation for children with Down syndrome yet the quality of life (QOL) domains important for this group have never been clearly articulated. This study investigated parental observations to identify QOL domains in children with Down syndrome and determined whether domains differed between children and adolescents. Method The sample comprised 17 families whose child with Down syndrome was aged 6–18 years. Primary caregivers took part in semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 21 publications
(27 reference statements)
4
56
0
2
Order By: Relevance
“…ID in children appeared to be associated with commonalities for QOL that are not restricted to a specific diagnosis. Similar to our study with Down syndrome (Murphy et al, ), we did not observe differences in the domains reported for children or adolescents.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…ID in children appeared to be associated with commonalities for QOL that are not restricted to a specific diagnosis. Similar to our study with Down syndrome (Murphy et al, ), we did not observe differences in the domains reported for children or adolescents.…”
Section: Discussionsupporting
confidence: 91%
“…For example, the CP QOL‐Child assesses emotional well‐being through how the child feels about themselves and their opportunities, although the current study suggests suitable items for a new measure would need to take into account behaviours such as frequency of smiling and those that indicate frustration, problems with impulse control, and aggression. Furthermore, the CP QOL‐Child omits potentially important domains of “predictability and routine” and “nature and outdoors.” In contrast, the domains identified in our study were remarkably consistent with those identified for children with Rett (Epstein et al, ) and Down syndromes (Murphy et al, ). ID in children appeared to be associated with commonalities for QOL that are not restricted to a specific diagnosis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Eleven domains were identified as important for children with Down syndrome including physical health, behaviour and emotion, personal value, communication, movement and physical activity, routines and predictability, independence and autonomy, social connectedness and relationships, variety of activities, nature and outdoors, and access to services. These parent‐reported domains provided rich descriptions of life experiences across the range of functional abilities found in Down syndrome and only data that were observable were coded to limit the reporting of parental emotion . The KIDSCREEN‐27 questionnaire arguably only includes four of these domains (physical well‐being; psychological well‐being; autonomy and parent relation; social support and peers) and therefore probably does not provide a complete picture of quality of life for children with Down syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…QOL assessment methods can be quantitative (Gomez, Verdugo, & Arias, ), qualitative (Murphy et al, ) or mixed method (Leonard et al, ). Assessment of individual well‐being and quality of life includes how a person perceives the physical, psychological and social dimensions of their lives.…”
Section: Introductionmentioning
confidence: 99%